Problemski in idejni aspekt esejistike Izidorja Cankarja - Štuhec, Miran (Slavistična revija, 2009)
The article discuses Izidor Cankar's essays from the point of view of their main thematic circles, taking into account their form in terms of the ideas and the view of art. The author maintains that the writer captured mumerous literature and art related topocs relevant in the first half of the 20th century. Of particular interest to him were the problem of style, relationship between the work of art and the reader or viewer, and the question how to define the ssence of a work of art.
Keywords: Cankar, Izidor; esejistika; literarne študije; slovenska književnost